Experiencias de vida del personal de salud frente al manejo del Plan de Atención de Emergencia ocurrida en Mocoa - Putumayo 2017 (2022)
Introduction: The life experiences of health personnel in managing the emergency care plan executed on March 31, 2017 in Mocoa Putumayo, where the weather phenomenon defined as Torrencial Avenue, was presented. Objective: The most relevant life experiences of the coordination and care of the emergency from the actions of immediate hospital care and from the approaches of Primary Health Care are analyzed: actions oriented to the individual and collective actions of public health based on the promotion health and disease prevention in the emergency and normalization phase. Method: To collect the information, an interview with open and semi-structured questions was conducted. Results: The findings show an articulated, intersectoral work and continuous communication, identifying relevant factors that allow success in the midst of chaos and pain, dedication to humanitarian work and resilience are also part of success. Conclusion: The compilation of these experiences can serve as a guide for health professionals in the event of disasters